2010
DOI: 10.5551/jat.3673
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factors II, V, IX, X, XI, and XII, Plasminogen, and α-2 Antiplasmin and Risk of Coronary Heart Disease

Abstract: Aim:To examine whether plasma levels of coagulation factors , , , , , and , plasminogen, and -2 antiplasmin are associated with coronary heart disease (CHD) in a prospective case-cohort study. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 14 publications
5
26
2
Order By: Relevance
“…32 In the prospective casecohort study of ARIC participants, the association of fXI:c with coronary heart disease was not significant when adjusted for Framingham risk factors. 33 In contrast, in the SMILE study, the risk of MI was increased for each quintile of fXI:c compared with the bottom quintile even after adjustment for cardiovascular risk factors and fXII:c levels. 31 Interestingly, although fXI:c and fXII:c levels were correlated, the opposite effects on risk for MI were also synergistic; therefore, the highest risk was found in men with both high fXI:c and low fXII:c. To explain this seeming paradox, the investigators suggested that any effect of fXII on risk of MI may not be mediated via fXI, but rather through some other mechanism.…”
Section: Fximentioning
confidence: 54%
See 1 more Smart Citation
“…32 In the prospective casecohort study of ARIC participants, the association of fXI:c with coronary heart disease was not significant when adjusted for Framingham risk factors. 33 In contrast, in the SMILE study, the risk of MI was increased for each quintile of fXI:c compared with the bottom quintile even after adjustment for cardiovascular risk factors and fXII:c levels. 31 Interestingly, although fXI:c and fXII:c levels were correlated, the opposite effects on risk for MI were also synergistic; therefore, the highest risk was found in men with both high fXI:c and low fXII:c. To explain this seeming paradox, the investigators suggested that any effect of fXII on risk of MI may not be mediated via fXI, but rather through some other mechanism.…”
Section: Fximentioning
confidence: 54%
“…No association was observed between fXII levels and coronary heart disease events, defined as hospitalized MI, a definite CHD death, proven silent MI, or a coronary vascularization. 33 It is evident from these studies that a firm conclusion on the role of fXII as a risk factor for MI is not established. It is possible that the discrepant results are explained by chance or other factors such as study design or case definitions.…”
Section: Fxiimentioning
confidence: 98%
“…Prospective cohort and case–control studies have demonstrated both positive correlation and no correlation of plasminogen, tPA, or PAI-1 with incident CAD and MI [4146]. Also, in the studies that found a positive correlation, the associations were not consistently independent of other cardiovascular risk factors [41, 43, 45, 46]. The relationship between OxPL-PLG and risk of future acute MI is less well studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence for an association between FXI levels in the general population and incident arterial thrombotic diseases has been inconsistent [47, 911, 13, 14]. Possible explanations for the discrepant results may include differences in study designs and assay methodologies, small sample sizes, inadequate control of confounding factors, reverse causation, or chance.…”
Section: Discussionmentioning
confidence: 99%
“…While elevated levels of FXI have been consistently positively associated with venous thromboembolism (VTE) [13] in epidemiologic studies, the relation of FXI to ischemic stroke (IS) [48], hemorrhagic stroke (HS) [7], myocardial infarction [4, 912], or coronary heart disease (CHD) [7, 13, 14] remains uncertain.…”
Section: Introductionmentioning
confidence: 99%